2017
DOI: 10.1016/j.econmod.2016.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Regulations and productivity: Long run effects and nonlinear influences

Abstract: This study estimates the impact of product market regulations on Total Factor Productivity (TFP) and distinguishes between its short run and long run effects. It also explores whether regulatory changes exert a nonlinear influence on TFP growth. The obtained empirical evidence reveals that in the long run lower regulations exert a significantly positive effect on TFP of OECD countries. Short run effects of regulation are not always statistically significant. The influence of regulatory changes is higher in cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Using data from U.S. companies from 1997 to 2010, Davies (2014) confirmed that the least regulated industries had the most significant gains in productivity and efficiency. In OECD countries, Papaioannou (2017) found that in the short run, regulation has no effect on total factor productivity (TFP) but rather found significantly positive long-run effects of light regulations on TFP. Some reported cases in West Africa suggest higher productivity among informal firms (Echevin and Murtin 2009), and also that informal firms can be more productive than formal firms especially where formal firms incur additional costs through regulations (Amin et al 2019).…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation
“…Using data from U.S. companies from 1997 to 2010, Davies (2014) confirmed that the least regulated industries had the most significant gains in productivity and efficiency. In OECD countries, Papaioannou (2017) found that in the short run, regulation has no effect on total factor productivity (TFP) but rather found significantly positive long-run effects of light regulations on TFP. Some reported cases in West Africa suggest higher productivity among informal firms (Echevin and Murtin 2009), and also that informal firms can be more productive than formal firms especially where formal firms incur additional costs through regulations (Amin et al 2019).…”
Section: 4mentioning
confidence: 99%
“…Using data from U.S. companies from 1997 to 2010, Davies (2014) confirmed that the least regulated industries had the most significant gains in productivity and efficiency. In OECD countries, Papaioannou (2017) found that in the short run, regulation has no effect on total factor productivity (TFP) but rather found significantly positive long‐run effects of light regulations on TFP.…”
Section: Literature Reviewmentioning
confidence: 99%